Cranky makes a friend [book with audioplayer] - Tran, Phuc, 1974- ([Library Ideas, LLC], 2025)
A new crane is on the construction site, and Lefty is smiley and talkative, the opposite of Cranky, making Cranky worry his friends will prefer Lefty over him, in a book about big trucks, big feelings and even bigger friendships.